Re-traumatization of torture survivors during treatment in somatic healthcare services: A mapping review and appraisal of literature presenting clinical guidelines and recommendations to prevent re-traumatization. (April 2023) - Schippert, Ana Carla S.P.; Grov, Ellen Karine; Dahl-Michelsen, Tone; Silvola, Juha; Sparboe-Nilsen, Bente; Danielsen, Stein Ove; Lie, Irene; Bjørnnes, Ann Kristin
Abstract: Rationale: The number of torture survivors is on the rise, posing issues for their care in healthcare settings. Even healthcare experts with training in refugee care are unaware of the health difficulties faced by torture survivors. Any medical evaluation or treatment has the potential to re-traumatize torture survivors, thereby reactivating trauma symptoms without applicable guidelines to prevent re-traumatization. Objective: Our objective was to identify, characterize, evaluate, and organize current, available evidence presenting existing recommendations and suggestions to prevent re-traumatization during the treatment of torture survivors' physical diseases in healthcare services. Methods: A comprehensive search of electronic databases was conducted. Gray literature coverage was obtained by searching for publications from relevant associations and healthcare organizations focusing on torture survivors. Clinical practice guidelines (CPGs) and research focusing on somatic healthcare services for adult torture survivors, regardless of study design, were eligible for review. Studies that concentrated on psychiatric departments were excluded. To conduct an overview of the available research and describe the scope and distribution of evidence, a mapping review methodology was used. Results: Forty out of 13, 111 initial citations met our criteria. There were two guidelines, and text and opinion statements predominated. Two authors independently assessed the risk of bias in each primary research study using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for the research design. Conclusions: This mapping review identifies triggers that may re-traumatize torture survivors during treatment and makes recommendations for prevention. Only a few studies have considered torture survivors' perspectives on treatment and re-traumatization. According to the findings of the mapping review, healthcare providers should consider survivors' biopsychosocial situations, demonstrate cultural sensitivity, and change theirpersonal attitudes . They must also identify tortured patients and determine when professional interpreters should be used.